Continuity, change and new ways of being: An exploratory assessment of farmer's experiences and responses to public health restrictions during the COVID‐19 pandemic in a rural Irish community. (17th February 2023) - O'Reilly, Alexis; Meredith, David; Foley, Ronan; McCarthy, Jack
Abstract: Farming occupations are, in the Global North, generally solitary, and a growing body of research identifies this as one of the factors that underpins low levels of wellbeing and poor mental health amongst farmers. The primary public health response to the coronavirus disease 2019 (COVID‐19) pandemic focused on reducing transmission of the virus by limiting interactions of people. This article seeks to assess the impact of these restrictions on farmer's experience of isolation and how it shaped their wellbeing. Applying a broad socio‐ecological framework, we analyse change, continuity and shifts in social and economic relations and their spatial reconfiguration during the COVID‐19 pandemic as recounted in semi‐structured, qualitative interviews. We found that while COVID‐19 has disrupted socio‐spatial relations, including key sites of socialisation for farmers and rural communities, occupational isolation was viewed as a positive feature of farming as was working in nature. Familial and informal networks of support were important throughout the pandemic, while novel engagements with communication technologies facilitated both change and continuity of social and economic interaction. Whilst these findings are broadly positive, the reconfiguration of, particularly, economic relations is viewed as accelerating the turn towards service delivery using technology and, consequently, further reducing opportunities for social interaction.